3D printing of all-regenerated cellulose material with truly 3D configuration: The critical role of cellulose microfiber. (15th October 2022) - Yuan, Rui; Wu, Kai; Fu, Qiang
Abstract: Direct ink writing, as a prospective three-dimensional (3D) printing technique, opens opportunities for offering high freedom to process cellulose into complex shapes. Current challenges are the accomplishment of dimensional accuracy of printed object and its truly 3D configuration, which put stringent requirements to the ink rheology that should be easily flowable under a suitable shear force while can rapidly recover to solid state after the force is removed. In this study, benefiting from the exquisite regulation of residual cellulose microfiber in a dissolved cellulose solution, a remarkable ink with excellent thixotropic property is prepared, which elaborately balance the traditional rheology tradeoff (extrudability and self-supporting) upon the formation of interconnected microfiber network. As a result, the optimized cellulose ink allows the printed object to successfully display arbitrary and truly 3D configurations, such as anatomical heart, ear, rabbit, lamp, and cup, and exhibit fine microstructure with a resolution of 250 μm. Graphical abstract: Unlabelled Image